Development of Interactive Multimedia based on Case Method Assisted by Articulate Storyline 3 in General Physics - Ida Wahyuni; Yeni Megalina; Ratna Tanjung; Khairul Amdani; Rajo Hasim Lubis (Postgraduate, University of Mataram, 2023)
Based on a survey of students in the PSPF D 2022 class, educators have 100% used smartphones, but some still use them to access things unrelated to learning. The general Physics course allocates three credits with two material credits and one practicum credit. The material can be conveyed thoroughly to students using learning media on Android smartphones, so learning media will be developed based on the Android smartphone operating system, namely Android-based interactive multimedia-based case method assisted by articulate storyline 3 in General Physics. This interactive multimedia will include several media consisting of RPS, material explaining everyday life, images, graphics, example problems, questions, learning videos, and student worksheets. This study aims to develop interactive multimedia that is feasible, practical, and effective and also to determine student responses. The research was conducted at the Physics Department of State University of Medan. This type of research uses the 4D models. The results of study show the percentage of assessment scores for interactive multimedia from material experts is 97% and media experts is 79.2%, the results of a practicality questionnaire 80%, and student responses according to the category 3.58 very effective, 3.61 very practical, 3.43 very safe, 3.38 very satisfied.